MODIFIKASI SEPIC CONVERTER UNTUK PENGONTROLAN TEGANGAN KELUARAN BERBASIS LOGIKA FUZZY - Al-Habsyi, Faisal; Fauzi, Rizana; Mahmudi, Irwan; Rahman, Yuli Asmi; Masarrang, Maryantho (Foristek, 2022)
Sun is one of the new renewable energy sources that can be used as a source of electrical energy that is available on the earth. But the sun in nature has a light intensity that varies greatly with each time and place. This issue can be overcome by using the Modification Sepic Converter tool with a fuzzy method to produce a stable electrical voltage so that it becomes usable electrical energy. This tool uses a series of converters connected to photovoltaics. The tool also uses a voltage sensor as feedback for the Fuzzy method to maintain a voltage of 21-23VDC to 48VDC.